Innovative impact planning and assessment through global libraries: Sustaining innovation during a time of transition. Issue 2 (8th August 2019) - Streatfield, David; Abisla, Richard; Bunescu, Violeta; Chiranov, Marcel; Garroux, Camila; Maister, Artiom; González Martín, Luis; Paley, Jeremy; Rae-Scott, Simon
Abstract : Purpose: The purpose of this paper is to report a range of innovative approaches, methods and tools for evaluating the impact of public libraries and supporting the development of library leaders drawn from projects supported by the Global Libraries initiative of the Bill and Melinda Gates Foundation. Design/methodology/approach: A range of approaches, tools and methods are described by specialist staff who were directly involved with these innovations. Findings: Some comments are provided on the effectiveness of these innovations. Research limitations/implications: All of these innovations have been tried out in public library settings, usually over a period of years. Practical implications: All of the selected innovations could be adapted and used by library leaders or impact specialists. Social implications: Several of the innovations are specifically designed to engage library staff and users in evaluation processes. Originality/value: The impact planning and assessment programme of GL was the largest sustained international public library evaluation programme so far attempted. This paper reports on the more innovative evaluation activities undertaken through this programme.